Radium girls [videorecording (DVD)] - King, Joey, 1999-; Quinn, Abby; Seymour, Cara; Shepherd, Scott (Juno Films, 2022)
Based on true events, it follows teen sisters, Bessie and Jo Cavallo, who dream of Hollywood and Egyptian pyramids as they paint luminous watch dials at the American Radium factory in New Jersey. When Jo loses a tooth, Bessie's world is turned upside down as a mystery slowly unravels. She discovers a corporate cover-up and, in a radical coming of age story, Bessie and the Radium Girls decide to take on American Radium. Based on historical events, the national sensation following the notorious case of the Radium Girls in 1928 ultimately led to a significant and lasting impact in the area of workplace health and safety and the study of radioactivity.